The evolution of primate vocal communication: a social route - Alban Lemasson; Camille Coye; Nancy Rebout; Florence Levréro (Revue de Primatologie)
There is no doubt that different factors determine the evolutionary trajectory of a species' communication abilities. Beyond habitat, social life is likely a selection pressure. The hypothesis positing that living in a complex social system requires complex communication skills has gained ground. However, the measures used classically to tackle this question (i.e. number of call types and group size) fail to capture some of the subtleties of the evolution of communication systems. Integrative approaches comparing closely related species to highlight the possible relationship between the characteristics of their social systems, their ecological niche and associated vocal communication systems are required to further our understanding of this evolutionary puzzle. We first addressed this topic in two sympatric guenons, Diana monkeys and Campbell’s monkeys. Interspecies competition, and the niche specialisations this creates, appeared to be a key evolutionary driver of their repertoires. While most of their vocal units were shared, we found a diversification of alarm calls and socially meaningful vocal combinations, as well as a differential use of inconspicuous (less detectable) call structures. This was linked to differences in group size and degree of exposition to predators. Secondly, we compared the acoustic structures in macaques belonging to four species with contrasting social styles. We found that tolerant (Tonkean and crested) macaques displayed higher levels of vocal diversity (number of vocal units) and flexibility (degree of gradation) than intolerant (Japanese and rhesus) macaques in agonistic and affiliative (but not neutral) contexts. Lastly, because the core of communication is represented not only by what is expressed by an isolated caller, but also by the way vocal interactions are structured, we explored ‘conversational rules’ in apes. We found no relationship between classical social (group size, interaction rates) and vocal (repertoire size, call rates) complexity metrics. However, close call interaction patterns differed in line with the nature of societies. Orang-utan, the most solitary species, preferentially used repeated and isolated calls apparently outside of any vocal interactions. Chimpanzee, the most competitive species displayed a high proportion of overlapping vocalisations. Vocal turn-taking predominated in the most tolerant species (bonobo and gorilla). Even if primate vocal repertoires change slowly over evolutionary time, making them good phylogenetic indicators, socio-ecological niches may induce considerable local divergence at different levels: vocal repertoire composition, acoustic structure and contextual use of calls, and vocal interaction patterns.